Contribution of constitutive characteristics of lipids and phenolics in roots of tree species in Myrtales to aluminum tolerance. Issue 1 (15th December 2016) - Maejima, Eriko; Osaki, Mitsuru; Wagatsuma, Tadao; Watanabe, Toshihiro
Abstract : High aluminum (Al) concentration in soil solution is the most important factor restricting plant growth in acidic soils. However, various plant species naturally grow in such soils. Generally, they are highly tolerant to Al, but organic acid exudation, the most common Al tolerance mechanism, cannot explain their tolerance. Lower phospholipid and higher sterol proportions in root plasma membrane enhance Al tolerance. Other cellular components, such as cell walls and phenolics, may also be involved in Al tolerance mechanisms. In this study, the relationships between these cellular components and the Al tolerance mechanisms in Melastoma malabathricum and Melaleuca cajuputi, both highly Al‐tolerant species growing in strongly acidic soils, were investigated. Both species contained lower proportions of phospholipids and higher proportions of sterols in roots, respectively. Concentrations of phenolics in roots of both species were higher than that of rice; their phenolics could form chelates with Al. In these species, phenolic concentrations and composition were the same irrespective of the presence or absence of Al in the medium, suggesting that a higher concentration of phenolics is not a physiological response to Al but a constitutive characteristic. These characteristics of cellular components in roots may be cooperatively involved in their high Al tolerance.